-5(1-5k)+5(-8k-2)=-4k-8k

Simple and best practice solution for -5(1-5k)+5(-8k-2)=-4k-8k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(1-5k)+5(-8k-2)=-4k-8k equation:


Simplifying
-5(1 + -5k) + 5(-8k + -2) = -4k + -8k
(1 * -5 + -5k * -5) + 5(-8k + -2) = -4k + -8k
(-5 + 25k) + 5(-8k + -2) = -4k + -8k

Reorder the terms:
-5 + 25k + 5(-2 + -8k) = -4k + -8k
-5 + 25k + (-2 * 5 + -8k * 5) = -4k + -8k
-5 + 25k + (-10 + -40k) = -4k + -8k

Reorder the terms:
-5 + -10 + 25k + -40k = -4k + -8k

Combine like terms: -5 + -10 = -15
-15 + 25k + -40k = -4k + -8k

Combine like terms: 25k + -40k = -15k
-15 + -15k = -4k + -8k

Combine like terms: -4k + -8k = -12k
-15 + -15k = -12k

Solving
-15 + -15k = -12k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '12k' to each side of the equation.
-15 + -15k + 12k = -12k + 12k

Combine like terms: -15k + 12k = -3k
-15 + -3k = -12k + 12k

Combine like terms: -12k + 12k = 0
-15 + -3k = 0

Add '15' to each side of the equation.
-15 + 15 + -3k = 0 + 15

Combine like terms: -15 + 15 = 0
0 + -3k = 0 + 15
-3k = 0 + 15

Combine like terms: 0 + 15 = 15
-3k = 15

Divide each side by '-3'.
k = -5

Simplifying
k = -5

See similar equations:

| 12x-3=13x-1 | | 8y=2x | | 100-x=-81 | | 7+q-7q-6q+3= | | 6a-17=4a+1 | | -7(2n-6)=7(n+3) | | 8=z-7 | | 3+9z-8h= | | 7x-8=3(x+2) | | 15x-9x=48 | | 8b-a=-3 | | 4(3d-2)=32 | | x^2+2x-52=0 | | -6(5+3x)=14 | | cos(6x)=cos(4x) | | 14.2=0.4(20m-7.8) | | 24+9=21 | | 24+9= | | a+4b=6 | | 12(2e+3)=96 | | -4z-5=8z+3 | | C=20n+8 | | (2z+9)(7-z)=0 | | f(x)=-8x^2+8x+9 | | y=x^2ln(3x) | | n+33=25 | | y=3*(-3)+10 | | -7r=7(8+3r) | | 5ksquared=180 | | x^2+4x-20y+50=0 | | 7t-8=7+t | | m-48=-18 |

Equations solver categories